Exchange rate pass-through in the Asian countries: does inflation volatility matter? - Soon, Siew View; Baharumshah, Ahmad Zubaidi; Wohar, Mark E. (Routledge, 2018)
This paper presents a nonlinear relationship between exchange rate pass-through (ERPT) and inflation volatility. Through the lens of a threshold framework, we uncover a clear evidence of near to one ERPT to consumer prices once inflation volatility crosses a threshold level of 4.17. Clearly, there are significant differences in the degree of ERPT between the high and low inflation volatility in the inflation targeting (IT) and non-IT Asian countries.